Isolation and purification of protactinium-231. (April 2018) - Jerome, S.M.; Collins, S.M.; Happel, S.; Ivanov, P.; Russell, B.C.
Abstract: Protactinium-231 is one of the lesser known actinides, yet the measurement of this radionuclide is central to dating studies in both paleoclimate and nuclear forensics measurements; furthermore, it is important as the immediate parent nuclide of the 227 Ac decay chain. In this paper, we present the preparatory work for an upcoming CCRI(II) supplementary comparison of this radionuclide. The material used in this work was of poorly known provenance, and it was necessary to carry out a chemical purification of this material prior to use. A new extraction chromatography resin, TK 400, which has been developed for the separation of 231 Pa, was tested at NPL. The aims of the work were achieved; the recovery of 231 Pa was ~85%, the decay products were recovered in good yield (~95%) and stable element impurities were removed. Highlights: This paper presents a new separation scheme for 231 Pa from its decay products. The use of a new extraction chromatography resin is evaluates. Measurement of 231 Pa in age dating and forensics measurements is described.